Dapagliflozin lowers blood pressure via regulating the sympathetic neural activity in the paraventricular nucleus of hypothalamus in normal mice - Dong, Meiyuan; Xu, Zhimin; Zhou, Ligang; Wen, Song (Frontiers in Endocrinology, 2026)
Background and aimsThe risk of heart failure (HF) is significantly higher in patients with type 2 diabetes mellitus (T2DM). Recent studies have shown that an imbalance in the sympathetic nervous system (SNS) is a target for sodium-glucose cotransporter-2 inhibitors (SGLT-2i), which have been proven to reduce the risk of adverse HF outcomes in several clinical trials. However, the specific central mechanisms involved remain unclear. Therefore, our research investigates how dapagliflozin (DAPA) regulates blood pressure through SNS and explores the central neural and endocrinological pathways by which DAPA, an SGLT-2i, influences SNS activity and its impact on the cardiovascular system in the treatment of HF in T2DM.Material and methodsTwenty-one male C57BL/6 mice aged 8–10 weeks were randomly divided into three groups (n = 7 each): control (CTRL), DAPA, and DAPA-Cyanine 3 (DAPA-Cy3). Blood pressure (BP), heart rate (HR), and blood glucose (BG) were measured after a single dose of treatment. DAPA-Cy3 was designed to assess its ability to cross the blood-brain barrier (BBB). Additionally, histological co-localization analyses of immunoreactivity for c-Fos, neuronal nitric oxide synthase (nNOS), corticotropin-releasing hormone (CRH), and vasopressin (VP) across groups were performed to explore how SGLT-2 inhibitors regulate the central sympathetic nervous system (SNS).Results1) DAPA significantly reduced both systolic blood pressure (SBP) and diastolic blood pressure (DBP) in mice, without notably affecting the heart rate (HR); 2) SGLT-2 was found to be extensively expressed in the central nervous system (CNS), especially in the hypothalamus and brainstem; 3) DAPA-Cy3 was able to cross the blood-brain barrier (BBB) and disperse throughout the brain; and 4) DAPA clearly influenced the activity of specific neurons expressing nNOS, CRH, and VP in the hypothalamus.ConclusionDAPA, as an SGLT-2 inhibitor, crosses the BBB and binds to the innate SGLT-2 in the hypothalamus and brainstem of mice. This significantly influences the tone of the SNS through indirect regulation by modulating nNOS, CRH, and VP, which are believed to be the upstream regulatory points of SGLT-2 in interacting with the SNS.